Analisis Perkembangan Eksport Dalam Menambah Cadangan Devisa Indonesia - Alwi, Ikhsan; Reza, Syahrul (JAMBIS : Jurnal Administrasi Bisnis, 2024)
Foreign exchange reserves are defined as the amount of foreign currency reserved by the central bank (Bank Indonesia) for the purposes of financing development and foreign obligations such as import financing and other financing to foreign parties. The problem in this research is: How is the progress of exports in increasing Indonesia's foreign exchange reserves? From the results of research conducted by the writer, it can be seen that the analysis of export progress in adding 1o Indonesia's foreign exchange reserves in 1995-2020 shows a positive expectation: when exports increase, foreign exchange reserves will also increase While imports have a negative expectation sign. when imports increase, foreign exchange reserves will decrease. From the results of the research above, the writer provides suggestions for the government to improve the Indonesian economy through increasing exports and reducing imports by expanding export destination countries and improving the quality of export products. Because of the excess of exports over imports, it will benefit the government by increasing foreign exchange reserves. In addtion, the government should reduce foreign debt, although at first it increasing foreign exchange reserves but it will reduce foreign exchange reserves for the debt payment, moreover the interest on the debt, and it is hoped that Bank Indonesia as the Central Bank will always maintain the condition of Indonesia's foreign exchange reserves so that international transactions can take place stably. The position of Indonesia's foreign exchange reserves is said to be safe if it has sufficient import needs for a period of at least three months of imports